Nitric Oxide Levels in Patients with Psoriasis Treated with Methotrexate - Nilgun Solak Tekin; Nilsel Ilter; Banu Sancak; Muge Guler Ozden; Mehmet Ali Gurer (Mediators of Inflammation)
Psoriasis is a chronic, recurrent, inflammatory, and hyperproliferative disease. Recently there have been studies regarding increases in the levels of NO in inflammatory dermatoses including psoriasis. In this study, 22 patients with psoriasis were scored with PASI (psoriasis area and severity index) and the levels of serum nitrite-nitrate were evaluated before and after therapy with methotrexate (Mtx). The results were compared with age- and sex-matched healthy volunteers. The relation of the results with the clinical severity and the cumulative Mtx dose were also evaluated. The serum levels of nitrite-nitrate of the psoriatic patients with active lesions were found to be significantly higher than the levels of the healthy volunteers and the patients after therapy. The elevated nitrite-nitrate serum levels in the inflammatory period may suggest the possible role of this mediator in the etiopathogenesis of psoriasis and the potential future use of NO inhibitors in the treatment of psoriasis.